Integrated management of collar rot (Sclerotium rolfsii) of brinjal (Solanum melongena) - D.P. KULDHAR and UTPAL DEY, A.P. SURYAWANSHI*, A.S. BORGAONKAR (Indian Phytopathology, 2015)
The studies were carried out on collar rot caused by Sclerotium rolfsii Sacc. on brinjal (Solanum melongena L.) during kharif 2012 at Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani. The in-vitro evaluation revealed highest average mycelial growth inhibition with fungicides, Vitavax (100.00%), Tebuconazole (99.25%) and Penconazole (99.03%). Of the bioagents and bioinoculants/PGPR evaluated, significantly highest mycelial growth inhibition was recorded with Bacillus megaterium (87.85%). Aqueous extracts of all botanicals tested (@ 10 and 20%) exhibited antifungal potential and significantly highest average mycelial growth inhibition was recorded with Azadirachta indica (71.17%) Significantly highest seed germination (80.00%) was recorded with the treatment Vitavax (ST @ 1.5g/kg) + Thiram (ST @ 1.5g/kg) + P. fluorescens (ST @ 10g/kg) + NSC (SA @ 50g/kg soil). Significantly highest reduction in pre-emergence (69.96%), post-emergence (55.43%) and average (62.37%) mortality were recorded with treatment of Vitavax + Thiram + P. fluorescens + NSC. Thus, it is concluded that brinjal collar rot can be managed effectively by seed treatment with fungicides (Vitavax, Thiram), bioagent (P. fluorescens) and soil amendment with neem seed cake.